Triple artemisinin-based combination therapy (TACT): advancing malaria control and eradication efforts - Emmanuel Kokori; Gbolahan Olatunji; Adeola Akinboade; Aminat Akinoso; Emmanuel Egbunu; Sikiru Ademola Aremu; Chuka Emmanuel Okafor; Olamide Oluwole; Nicholas Aderinto (Malaria Journal, 2024)
Abstract This paper examines the far-reaching implications of Triple Artemisinin-Based Combination Therapy (TACT) in the global battle against malaria. Artemisinin-Based Combination Therapy (ACT) is recognized for its cost-effectiveness, lower likelihood of adverse events, and widespread acceptance by patients and healthcare providers. However, TACT introduces novel dimensions to the fight against malaria that make them a superior choice in several aspects. TACT has been demonstrated to address resistance, offer a broader spectrum of action, reduce the risk of treatment failure, and can be tailored to meet regional needs, strengthening the global effort to combat malaria. However, maximizing these benefits of TACT depends on accessibility, particularly in resource-limited regions where malaria is most prevalent. Collaborative efforts among stakeholders, sustainable pricing strategies, efficient supply chains, and public–private partnerships are essential to ensure that TACT reaches needy populations. Moreover, dispelling prevalent malaria myths through health education campaigns is critical in this endeavour. The paper underscores the significance of collaborative initiatives and partnerships among governments, international organizations, research institutions, acadaemia, pharmaceutical companies, and local communities. Together, these efforts can pave the way for the acceptance, adoption, and success of TACT, ultimately advancing the global goal of a malaria-free world.